2012
DOI: 10.1111/j.1600-0854.2012.01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Tomography Reveals Rab6 Is Essential to the Trafficking of transGolgi Clathrin and COPICoated Vesicles and the Maintenance of Golgi Cisternal Number

Abstract: We have shown previously that Rab6, a small, trans-Golgi-localized GTPase, acts upstream of the COG and ZW10/RINT1 retrograde tether complexes to maintain Golgi homeostasis. Here, we present evidence from the unbiased and high-resolution approach of electron microscopy and electron tomography that Rab6 is essential to the trans-Golgi trafficking of two morphological classes of coated vesicles; the larger corresponds to clathrin-coated vesicles and the smaller to COPI-coated vesicles. Based on the site of coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
103
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(129 citation statements)
references
References 67 publications
(140 reference statements)
24
103
1
Order By: Relevance
“…Mammalian Rab6 has been shown to localize and function in the TGN for the fusion of endosome-derived vesicles (13). However, Ypt6 does not appear to localize exclusively to TGN, because more than 50% of GFP-Ypt6 fluorescence overlaps with the cis-Golgi marker Sed5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian Rab6 has been shown to localize and function in the TGN for the fusion of endosome-derived vesicles (13). However, Ypt6 does not appear to localize exclusively to TGN, because more than 50% of GFP-Ypt6 fluorescence overlaps with the cis-Golgi marker Sed5.…”
Section: Resultsmentioning
confidence: 99%
“…In mammalian cells, accumulating evidence suggests that Rab6 localizes at the trans-Golgi region and functions in retrograde protein transport and in Golgi structural organization (13,14). Ypt6 may very well function in the yeast Golgi maintenance.…”
mentioning
confidence: 99%
“…5). Interestingly, when mammalian cells are depleted of the Rab6 GTPase, secretion slows and the number of Golgi cisternae per stack increases (Storrie et al, 2012). It is possible that Rab6 depletion increases the persistence time of Golgi cisternae.…”
Section: Discussionmentioning
confidence: 99%
“…Through a slow transport pathway, Shiga toxin lacking a KDEL retrieval sequence and the Golgi-resident galactosyltransferase can reach the ER in a Rab6A-dependent manner (Girod et al 1999). The further analysis of the pathway is hampered by the fact that Rab6 is also involved in COPI-and clathrin-dependent trafficking steps at the Golgi (Storrie et al 2012), demanding careful dissection of the different roles of Rab6A and illustrating the need to identify Rab6A effectors specific for an individual pathway. To complicate the issue, Rab6-COPI-independent (Chen et al 2003) and Rab6-COPI-dependent pathways have also been reported (Smith et al 2009) that appear to function in parallel with the classical COPI retrograde Golgi-ER pathway.…”
Section: Copi-independent Transport Carriersmentioning
confidence: 99%